2011
DOI: 10.1038/ki.2010.535
|View full text |Cite
|
Sign up to set email alerts
|

The induction of macrophage hemeoxygenase-1 is protective during acute kidney injury in aging mice

Abstract: Aging is thought to be associated with a higher susceptibility to renal ischemia-reperfusion injury (IRI). To study whether defective induction of hemeoxygenase-1 (HO-1, a protective and anti-inflammatory enzyme) might contribute to this, we found that while 12-month-old mice had similar baseline renal function and HO-1 expression, the induction of HO-1 usually seen in ischemia-reperfusion was reduced. This was also associated with worsened renal function and acute tubular necrosis in the aged compared with yo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
66
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(75 citation statements)
references
References 44 publications
6
66
2
1
Order By: Relevance
“…19,[60][61][62] This finding may reflect the innate phase response by tolerogenic rMoPh utilizing counter-regulators such as single Ig receptor-related protein, 63 IFN regulatory factor 4, 64 adenosine 2A receptor, 65 hemeoxygenase-1, 56,62 and Fc g-receptor. 66 Secretion of IL-10 by resident rMoPh is emerging as one of the key effectors of cytoprotection, 61,66 raising the possibility of therapeutically augmenting this secretion by rMoPh to enhance cytoprotection.…”
Section: Functions Of Rmoph In Surveillance Tolerance and Tissue Cymentioning
confidence: 90%
See 1 more Smart Citation
“…19,[60][61][62] This finding may reflect the innate phase response by tolerogenic rMoPh utilizing counter-regulators such as single Ig receptor-related protein, 63 IFN regulatory factor 4, 64 adenosine 2A receptor, 65 hemeoxygenase-1, 56,62 and Fc g-receptor. 66 Secretion of IL-10 by resident rMoPh is emerging as one of the key effectors of cytoprotection, 61,66 raising the possibility of therapeutically augmenting this secretion by rMoPh to enhance cytoprotection.…”
Section: Functions Of Rmoph In Surveillance Tolerance and Tissue Cymentioning
confidence: 90%
“…30,93 More recent studies show that bone marrow-derived Mø or rMoPh display biphasic expression of proinflammatory factors followed by anti-inflammatory and reparative factors in response to challenge with lipopolysaccharide or ischemic injury, respectively. 62,92,94,95 Within the kidney, specific paracrine factors released from renal parenchymal cells, such as IL-10, DAMPs, or apoptotic bodies, initiate or augment this phenotypic reprogramming of rMoPh. 90,96,97 Figure 2.…”
Section: Plasticity Of Function Of Rmoph During Renal Injury and Repairmentioning
confidence: 99%
“…[30][31][32][33][34][35][36][37][38] In particular, HO1 is essential for the regulation of redox pathways and catabolism of heme. 31,39 Here, we show that endotoxin preconditioning upregulated HO1 and SIRT1 in F4/80-positive macrophages (Figure 8).…”
Section: Macrophages In the Kidneys Of Preconditioned Mice Have Incrementioning
confidence: 99%
“…31,49 The expression of HO-1 is always correlated with a better prognosis after ischemic damage. [50][51][52] We found that mice injected with GTCs showed a strong upregulation of HO-1 2 days after renal damage induction. This finding suggests that HO-1 upregulation induced by GTCs could be involved in kidney protection from IRI.…”
Section: Discussionmentioning
confidence: 76%